12x-x=55 2(x+3)=16 5(x+3)+7=3(x+12)

12x-x=55 2(x+3)=16 5(x+3)+7=3(x+12)

  • 12x-x=55
    11x=55
    x=55/11=5

    2(x+3)=16
    2x+6=16
    2x=16-6=10
    x=10/2=5

    5(x+3)+7=3(x+12)
    5x+15+7=3x+36
    5x-3x=36-22=14
    2x=14
    x=14/2=7

  • 12х-х=5511х=55Х=55:11Х=512*5-5=5555=552(x+3)=162х+6=162х=16-62х=10Х=10:2Х=52(5+3)=1616=165(x+3)+7=3(x+12)5х+15+7=3х+365х-3х=36-15-72х=14Х=14:2Х=75(7+3)+7=3(7+12)57=57

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *